(untitled) (Journal of Forensic Medicine & Toxicology, 2016)
Close range shot gun wounds of head produce a very devastating injury leading to evisceration of brain. Many a times it is misinterpreted as explosion injury. The current case discusses autopsy features and mechanism of this injury caused to a 12 year old boy who while playing misfired the shotgun accidentally and succumbed to death.